ByzRev 02.2020.002: Anthony Kaldellis, Romanland. Ethnicity and Empire in Byzantium: Cambridge, Massachusetts: The Belknap Press of Harvard University Press 2019. - Dimitriadis, Stefanos (The Byzantine Review, 2020)
Anthony Kaldellis, Romanland. Ethnicity and Empire in Byzantium. Cambridge, Massachusetts: The Belknap Press of Harvard University Press 2019. 373 pp. - ISBN: 978-0-674-98651-0 (Hardcover € 40,50)